PERAN PENDIDIKAN MULTIKULTURAL DALAM MENCIPTAKAN KESADARAN HUKUM MASYARAKAT PLURAL - Ahmad Lonthor (IAIN Ambon, 2021)
This study examines the role of multicultural education in creating legal awareness of plural societies. Data was collected through library research using a statutory approach (statue approach), a conceptual approach and a comparative approach. The results show that there is a strong relationship between education and legal awareness, where education is the basis for human development with legal awareness, because legal awareness itself is not a scientifically formed condition in humans, however humans have reason as their natural potential to form legal awareness. with the form of knowledge, understanding, attitudes and behavior. The attainment of the system of thinking or reasoning goes through an educational process. Multicultural education itself aims to create legal awareness of plural society as an effort to strengthen the legal system in Indonesia, so that it can create tolerance, understanding and knowledge that takes into account cultural differences, as well as differences and similarities between cultures and their relation to world views, concepts, values, beliefs, and attitudes. Keywords: multicultural education, legal awareness, plural society